Concomitant activation and antigen uptake via human Dectin-1 results in potent antigen-specific CD8(+) T cell responses - Ni, Ling (2010)
Dectin-1, a C-type lectin recognizing fungal and mycobacterial pathogens, can deliver intracellular signals that activate dendritic cells (DCs), resulting in initiation of immune responses and expansion of Th17 CD4(+) T cell responses. Here, we studied the roles of human Dectin-1 (hDectin-1) expressed on DCs in the induction and activation of antigen-specific CD8(+) T cell responses. We first generated an agonistic anti-hDectin-1 monoclonal antibody (mAb), which recognizes the hDectin-1 Glu(143)-Ile(162) region. It bound to in vitro monocyte-derived DCs and to in vivo CD1c(+)CD1a(+) dermal DCs, but not to epidermal Langerhans cells. Anti-hDectin-1-mediated DC activation resulted in upregulation of costimulatory molecules and secretion of multiple cytokines and chemokines in a Syk-dependent manner. DCs activated with the anti-hDectin-1 mAb could significantly enhance both neo and foreign antigen-specific CD8(+) T cell responses by promoting both the expansion of CD8(+) T cell and their functional activities. We further demonstrated that delivering antigens to DCs via hDectin-1 using anti-hDectin-1-antigen conjugates resulted in potent antigen-specific CD8(+) T cell responses. Thus, hDectin-1 expressed on DCs can contribute to the induction and activation of cellular immunity against intracellular pathogens, such as mycobacteria, that are recognized by DCs via Dectin-1. Vaccines based on delivering antigens to DCs with an agonistic anti-hDectin-1 mAb could elicit CD8(+) T cell-mediated immunity.